Performance measurement: learning from the past and projecting the future - Bourne, Mike (Emerald Group Publishing Limited, 2008)
Abstract Purpose – This paper aims to review the developments in performance measurement over the last 20 years, reflecting on the past and projecting into the future. Design/methodology/approach – The author presents a personal reflection on research and practice. Findings – The paper identifies seven issues for management, seven issues for research and three enduring dilemmas. Originality/value – The paper highlights a number of areas where developments from academic and practitioner co-creation have not been widely adopted in p
Keywords: Business performance; Performance measures; Balanced scorecard